The Relationship Between Nutritional Status, Maternal Knowledge, and Family Socio-Economic Status with The Development of Children Aged 3-5 Years at UPTD Puskesmas Brang Rea - Pebrian, Legi Silsa; Surasmaji, Lalu Irawan; Nirmala, Suci; Hidayati, Sulatun (Jurnal Biologi Tropis, 2025)
Early childhood development, particularly in the age range of 3-5 years, is a critical period marked by rapid physical growth and psychosocial development. Various factors can influence a child’s development, including nutritional status, maternal knowledge, and family socio-economic conditions. To determine the relationship between nutritional status, maternal knowledge, and family socio-economic status with the development of children aged 3-5 years at UPTD Puskesmas Brang Rea. This research employed a quantitative, observational analytic approach with a cross-sectional design. A purposive sampling technique was used. The study was conducted at UPTD Puskesmas Brang Rea in September 2024, involving 100 respondents. Data were analyzed using the Chi-square test with a significance level of p < 0.05. From a total of 100 respondents, the univariate analysis revealed that 38% of children had good nutritional status, 58% of mothers had high knowledge levels, 53% of children belonged to low socio-economic families, and a majority of children (36%) showed questionable developmental progress. Bivariate analysis indicated a significant relationship between nutritional status and child development (p-value 0.002), maternal knowledge and child development (p-value 0.047), and family socio-economic status and child development (p-value 0.020). There is a significant relationship between nutritional status, maternal knowledge, and family socio-economic status with the development of children aged 3-5 years at UPTD Puskesmas Brang Rea.